2021
DOI: 10.1021/accountsmr.0c00075
|View full text |Cite
|
Sign up to set email alerts
|

Refining Grains of Metals through Plastic Deformation: Toward Grain Size Limits

Abstract: Conspectus Refining grains of metals and alloys is an effective approach to tailor their properties and performance. Plastic deformation is routinely used for structure refinement, with which microstructures down to the submicron scale can be accessed in most metals and alloys. However, further reducing grain sizes below the submicron scale is challenging. Grain refinement induced by deformation is basically a process of generating grain boundaries (GBs) through interaction of dislocations and/or other defects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…It is known that severe plastic strain leads to grain refinement. [ 19,44,45 ] Here, the FCC grain size decreases after yielding, and its final size is close to the BCC grain size. Finally, the comparison of the stress−strain curve obtained through theoretical model calculation and experiments is shown in Figure 8b.…”
Section: Resultsmentioning
confidence: 76%
“…It is known that severe plastic strain leads to grain refinement. [ 19,44,45 ] Here, the FCC grain size decreases after yielding, and its final size is close to the BCC grain size. Finally, the comparison of the stress−strain curve obtained through theoretical model calculation and experiments is shown in Figure 8b.…”
Section: Resultsmentioning
confidence: 76%
“…GB relaxation is observed not only in Cu, but also in other FCC metals with higher stacking fault energies (such as Ni and Al) and metals with lower stacking fault energies (Ag). The GB relaxation found in the nanograined metals indicated that below a critical grain size, the dislocation motion changes and interacting with dislocations will also change the GB state simultaneously [18,19]. The extensivelyexisting GB structure modification and GB relaxation in nanograined metals prepared by plastic deformation can be utilized to develop stable nanostructured metals and alloys for high temperature applications.…”
Section: Gb Relaxation (< 70 Nm)mentioning
confidence: 99%
“…polymers and metals, with the critical lengths of polymers passing the entanglement limit and the metal grain sizes over several nm. 1,2 As model systems for the studies of general material physics, granular materials, composed of densely packed nano-or macro-scale particles, demonstrate unique impact-and shock-resistant properties that are highly dependent on the sizes, morphologies and surface structures of the building units. [3][4][5] When their sizes approach the tens of nanometer scale, the dynamics of particles can be manipulated by the complex interactions among the particles in their assemblies, giving rise to unexpected and oen exceptional mechanical performances.…”
Section: Introductionmentioning
confidence: 99%